Splitting Business Logic. Container for Analytical Business Logic - Murdjeva, Aleksandrina (Research Papers, 2009)
This study is an examination of the possibilities to split the business logic of information system between the different layers in the application architecture and the existing alternatives to realize the business logic. In the analysis are discussed the alternatives from the point of view of the possibilities, that they give to the developers and users of the system, to reuse, optimize and maintain the business logic.On the ground of the given analysis in the study is proposed new definition for the term “business logic”. This new definition looks at the structure of the business logic and is a very important ground to make more extensive research of the components and their native place for “living”, for realization.To make decision about the better place for the business logic components, are necessary to define a clear set of criteria to classify the elements of information systems as some kind business logic. The study makes some proposition about such criteria set and use them to define two major kinds of business logic – transaction business logic and analytical business logic. For each of them are given values for the criteria, that easy to find.Further in the paper for one of the business logic kinds, exactly then one called “analytical business”, are made more extensive research. The results of the research are in the direction to explore the weakness of existing technology and approaches to realize this kind of business logic. The points of view here again are optimization, reuse and maintenance. To overcome the weaknesses in the study is introduced a new idea to put a new level, a new component in the application architecture. This new component is called “container for analytical business logic” and his purpose is to manage the analytical business logic so that to ensure the existence of the component in only one place and to give access to different (as purpose, as realization) elements. As argument of the acceptability of this idea in the study also is proposed a concrete instrument to realize the container and as such instrument are chosen stored procedures. To illustrate better the functionality and the use technology of the container is given a set of prototypes of packages and stored procedures as a mainframe as possible and very native instrument for realization of the architecture component.